An explanation of the methanogenic pathway for methane production in anaerobic digestion of nitrogen-rich materials under mesophilic and thermophilic conditions. (September 2018) - Yin, Dong-Min; Westerholm, Maria; Qiao, Wei; Bi, Shao-Jie; Wandera, Simon M.; Fan, Run; Jiang, Meng-Meng; Dong, Ren-Jie
Graphical abstract: Illustrations of the methanogenic pathways indicated by carbon isotope (δ 13 C) analysis under mesophilic and thermophilic conditions. Highlights: The Methanogenesis pathway was quantitatively determined by 2–13C isotope. SAO-HM account for 41% and 50% of methane formation at 37 °C and 55 °C. The thermophilic digester had 15% lower methane yield rates. Stable processes were achieved at free ammonia of 31 and 145 mg/L, respectively. Abstract: The impact of temperature on the anaerobic digestion of chicken manure was investigated by studying the process performance and pathway for continuously-fed digesters under mesophilic and thermophilic conditions. The mesophilic digester obtained a 15% higher methane yield compared with the thermophilic digester. Mesophilic and thermophilic digester had free ammonia of 31 and 145 mg/L, respectively. The stable carbon isotope analysis indicated that 41% and 50% of acetate was converted to methane through the syntrophic acetate oxidation and hydrogenotrophic methanogenesis (SAO-HM) pathway under mesophilic and thermophilic conditions, respectively. The genus Pseudomonas represented 10% and 16% under mesophilic and thermophilic conditions, respectively. A high abundance of the methanogens genus Methanoculleus (94% of total methanogens) in mesophilic and the genus Methanothermobacter (96%) in thermophilic digesters indicated they were the main hydrogenotrophic partners in SAO. The present study therefore illustrated that methanogenic pathway shifting, induced by free ammonia, closely correlated to the process performance.